(untitled) (FUDMA Journal of Agriculture and Agricultural Technology, 2026)
This study assessed the status of soil degradation across three prevalent land uses; farmland, grazing land, and tree plantations in Kumbotso Local Government Area, Kano State, where a total of eighteen (18) samples (six per land use) using simple random soil sampling methods were collected within the depths of 0-20 cm and composites of two samples for each land use were made and tested for physical (bulk density, texture) and chemical (N, P, K, ESP, BSP, EC, OM) properties. The laboratory results obtained were compared with the standard indicators and criteria for land degradation assessment according to FAO, 1979. The results revealed varying degrees of degradation; physical degradation was evident with tree plantations and grazing lands exhibiting higher bulk density (1.4–1.7 g cm⁻³). Most soils textureof the area were sandy (>85% sand), though some farmlands showed improved silt content (120–130 g kg⁻¹). Chemical degradation was discerned with low P (6.16–51.9 mg kg⁻¹), N (0.1–0.19%), and K (0.33–0.43 cmol/kg) respectively, organic matter depletion (0.58–1.91%) and BS below (1%) signifying very high degradation were observed, while some sites have shown high ESP (up to 31%). EC values in all the sites are within the standard (< 2 dS/m). From the findings, the comparison of the status of the soil’s physical and chemical properties with the FAO standard shows that the area is undergoing degradation. Therefore, sustainable land management strategies, including rotational grazing, organic amendments, gypsum application, and agroforestry, were recommended to enhance the soil structure and fertility of the study area. Additionally, policy interventions for promoting soil conservation and farmer education are also needed to combat ongoing degradation and ensure long-term agricultural productivity.